Strategi Guru Pendidikan Agama Islam dalam Pembinaan Akhlak Mulia Siswa di SMA Negeri 1 Sosa Kabupaten Padang Lawas - Siti Masgorgor (Studi Multidisipliner: Jurnal Kajian Keislaman, 2020)
This research discussed in the strategy carried out by Islamic religious education teachers in fostering noble morals of students and the efforts made to overcome  the problems faced in developing the noble morals of students at SMA Negeri 1 Sosa, Padang Lawas Regency. The results concluded that the strategy carried out by Islamic religious education teachers in fostering the noble character of students atas SMA Negeri 1 Sosa, Padang Lawas district is carried out in learning activities, school culture development, and extracurricular activities using exemplary methods, planting and enforcing discipline, habituation, guiding and advising students, fulfilling the rights of students and treating students fairly. Efforts made to overcome the problems faced in fostering noble morals of students are through positive activities (intracurricular, co-curricular, and extracurricular), increasing cooperation with parents, community leaders and relevant agencies